Can quantitative susceptibility mapping help diagnose and predict recovery of concussion in children? An A-CAP study. Issue 3 (14th December 2022) - Sader, Nicholas; Gobbi, David; Goodyear, Brad; Frayne, Richard; Ware, Ashley L; Beauchamp, Miriam H; Craig, William R; Doan, Quynh; Zemek, Roger; Riva-Cambrin, Jay; Yeates, Keith Owen
Abstract : Background: Quantitative susceptibility mapping (QSM) is an MRI technique that is a potential biomarker for concussion. We performed QSM in children following concussion or orthopaedic injury (OI), to assess QSM performance as a diagnostic and prognostic biomarker. Methods: Children aged 8–17 years with either concussion (N=255) or OI (N=116) were recruited from four Canadian paediatric emergency departments and underwent QSM postacutely (2–33 days postinjury) using 3 Tesla MRI. QSM Z-scores within nine regions of interest (ROI) were compared between groups. QSM Z-scores were also compared with the 5P score, the current clinical benchmark for predicting persistent postconcussion symptoms (PPCS), at 4 weeks postinjury, with PPCS defined using reliable change methods based on both participant and parent reports. Results: Concussion and OI groups did not differ significantly in QSM Z-scores for any ROI. Higher QSM Z-scores within frontal white matter (WM) independently predicted PPCS based on parent ratings of cognitive symptoms (p=0.001). The combination of frontal WM QSM Z-score and 5P score was better at predicting PPCS than 5P score alone (p=0.004). The area under the curve was 0.72 (95% CI 0.63 to 0.81) for frontal WM susceptibility, 0.69 (95% CI 0.59 to 0.79) for the 5P score and 0.74 (95% CI 0.65 to 0.83) for both. Conclusion: The findings suggest that QSM is a potential MRI biomarker that can help predict PPCS in children with concussion, over and above the current clinical benchmark, and thereby aid in clinical management. They also suggest a frontal lobe substrate for PPCS, highlighting the potential for QSM to clarify the neurophysiology of paediatric concussion.